Cultural Psychology: A Once and Future Discipline by Michael Cole. Harvard University Press, 1996. 400 pages. (American Journal of Islam and Society, 1998)
For the past thirty years, Michael Cole has been a prolific writer, researcher,and creative thinker in the field of developmental psychology. In CulturalPsychology: A Once and Future Discipline, he attempts to synthesize what hehas learned and to set forth an approach to developmental psychology from anhistorical and culrural perspective. Hence, a culturally sensitive science ofhuman development appears to be Cole's objective. He describes cultural psychologyas "the study of culture's role in the mental life of human beings." Hissubtitle suggests that culrural psychology was a discipline which existed in formertimes and will exist again in the future. Cole argues in favor of what isknown as a "second psychology," which moves beyond the confines of traditionaland contemporary psychological thinking about how the human mind isunderstood. The former psychology, described as naturalistic, has focused onthe familiar and more classical views. Such views evolved from our analysis ofmental phenomena developed from ideas, sensations, reflexes, and experienceswith sensorimotor connections. Alternately, the latter approach, "second psychology,"looks at the higher mental processes formed by cultures. Theseinclude things such as languages, myths, and social practices within the individual'ssocial context. The author reviews the evolution of thought throughseveral contemporary thinkers who, in his view, have contributed the substanceof a scientific, second psychology-oriented methodology necessary for aviable, efficacious culrural psychology. That is to say a psychology which issensitive to social and culrural contexts. The context includes such things aslanguage, riruals, and routines as they contribute to understanding people interms of their interdependence, cooperation, and essential humanity ...